PENGARUH SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG BEKATUL BERAS (RICE POLISH) PADA PEMBUATAN MIE BASAH TERHADAP KADAR AIR DAN TINGKAT KESUKAAN KONSUMEN - Duka, Febby; Djasibani, Hemy R.; Lobo, Anita T. Dimu; Nahak, Maria H. (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Rice bran flour is flour made from rice bran which is divided into three types based on color, namely white, red and black rice bran flour. This study aims to determine the effect of substituting wheat flour with rice bran flour in making wet noodles on moisture content and consumer liking. This study used a factorial group randomized design in which the grouping was based on the use of different rice bran flours (white, red and black) with 5 treatments, namely 10 g, 20 g, 30 g, 40 g and 60 g rice bran flour. The observed variables were moisture content, color, texture, aroma and taste. The data obtained were analyzed using Analysis of Variance (Anova) and continued with Duncan's Multiple Range Test. The results of the analysis showed that each group gave a significant effect (fhit> 5%, < 1%) and each treatment of rice bran flour substitution gave a very significant effect (fhit> 1%) on the moisture content, color, texture, aroma and taste of wet noodles. Treatment A is a treatment that is highly preferred by consumers, with an average value of color 2.63, texture 2.87, aroma 2.97 and taste 2.90 with the lowest water content of 55.66%.